From Big Bang to Mario Mieli (Balthazar, 2022)
What do Mario Mieli and Stephen Hawking have in common? What do have in common a dissertation in Moral Philosophy - titled Towards a Gay Communism. Elements of a Homosexual Critique - and a best seller which popularized modern cosmological theory about the origin and evolution of the universe? The capacity to push the boundaries and to pave the way to unforeseen possibilities.
Keywords: Mario Mieli; Stephen Hawking; Elements of a homosexual critique; Abracadabra - incantesimi di Mario Mieli